Evaluating essential health packages from a human rights perspective. Issue 2 (3rd April 2017) - Chapman, Audrey R.; Forman, Lisa; Lamprea, Everaldo
ABSTRACT: Many countries at all levels of development have formulated an essential health package, sometimes also referred to as a health benefit plan or a health benefit basket. As defined by the World Health Organization (WHO), essential health packages (EHPs) are "health service interventions that are considered important and that society decides should be provided to everyone." Although EHPs are not often formulated from an explicitly human rights perspective, since they are conceptualized as a guaranteed minimum of health services, much like core health obligations, they have obvious human rights import. This article evaluates the principles from which the plans are developed, the content of the packages, and the experience of countries seeking to implement them from a human rights perspective. In the process, it seeks to gain greater clarity about the health service requirements of the right to health.